2009
DOI: 10.1089/jwh.2008.1133
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Behavior of Women with Self-Reported Distressing Sexual Problems

Abstract: Our results suggest inadequacies in the U.S. medical care system in addressing sexual problems in women. Gynecologists and primary care physicians, by including discussions about sexual health during routine visits, can increase the likelihood that adequate care can be offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
73
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 22 publications
8
73
0
4
Order By: Relevance
“…When women did not tend to perceive others as trustworthy and dependable (other-model), they tended to show less positive HSA. Even if positive HSA and recognition of the need for external help are more common in women than in men (Ang et al, 2004), receiving psychological help is not common in women (Shifren et al, 2009). A negative othermodel seems to be one of the factors that decreases women's positive HSA.…”
Section: Discussionmentioning
confidence: 93%
“…When women did not tend to perceive others as trustworthy and dependable (other-model), they tended to show less positive HSA. Even if positive HSA and recognition of the need for external help are more common in women than in men (Ang et al, 2004), receiving psychological help is not common in women (Shifren et al, 2009). A negative othermodel seems to be one of the factors that decreases women's positive HSA.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, time constraints were the predominant reason that prevented members of both the BSUG and AUGS from screening. Many studies report that healthcare professionals do not frequently address sexual issues with their female patients for various reasons [14,15]. The responses of Arab Gyns probably represent a lack of knowledge and weak sexual history-taking skills.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Shifren et al, (2009), women have often been reluctant to seek help for sexual problems hence we did not recruit through health professionals or clinics. Participant details are provided in Table 1 (pseudonyms have been used to protect anonymity).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, research has shown that treatment emergent sexual problems are infrequently discussed by GP's and mental health clinicians; personal discomfort, lack of time or expertise, and the belief that treatment options are limited have been cited as prohibitive factors (Goldstein, Lines, Pyke & Scheld, 2009;Quinn et al, 2011;Shifren et al, 2009). In addition, Quinn et al (2011) highlighted that fear of non-adherence has prompted the deliberate withholding of information about adverse sexual effects in spite of findings revealing such knowledge can actually improve adherence rates (Smith & Henderson, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation